2019
DOI: 10.22207/jpam.13.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extracts in Probiotic Encapsulation: Evaluation of their Effects on Strains Survivability in Juice and Drinkable Yogurt During Storage and an in-vitro Gastrointestinal Model

Abstract: The present study concerned with the evaluation of the adding value from the addition of plant extracts, including those from moringa, fennel, sage and green tea, during alginate encapsulation on the viability of probiotic bacteria (L. plantarum DSM 20205 and P. acidilactici DSM 20238) in fruit juice (i.e., kiwi, prickly pear and carrot juice) and drinkable yoghurt throughout storage at 4°C. The results revealed that the survival rates of L. plantarum DSM 20205 and P. acidilactici DSM 20238 cells encapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, through cross-linking gelation method, the addition of alginate encapsulation of Lactobacillus plantarum (9.32–9.58 Log10 CFU/g) and Pediococcus acidilactici (9.82–9.81 Log10 CFU/g) with Moringa oleifera extract (0.05–0.1%) in fruit juice and drinkable yogurt was evaluated. After 28 days of storage, the plant extract increased bacterial stability compared with the control in both products [ 87 ]. Table 1 shows the most-used encapsulation techniques for different bioactive compounds from M. oleifera and their possible applications.…”
Section: Encapsulation Methods Of Bioactive Compounds From ...mentioning
confidence: 99%
“…Moreover, through cross-linking gelation method, the addition of alginate encapsulation of Lactobacillus plantarum (9.32–9.58 Log10 CFU/g) and Pediococcus acidilactici (9.82–9.81 Log10 CFU/g) with Moringa oleifera extract (0.05–0.1%) in fruit juice and drinkable yogurt was evaluated. After 28 days of storage, the plant extract increased bacterial stability compared with the control in both products [ 87 ]. Table 1 shows the most-used encapsulation techniques for different bioactive compounds from M. oleifera and their possible applications.…”
Section: Encapsulation Methods Of Bioactive Compounds From ...mentioning
confidence: 99%
“…storage, as stated byShehata et al (2019) andJasińska et al (2018).Moreover, the low viable cell count (<6 log CFU/ml) displayed by Lai, Lai, et al (2020), Yee et al (2019), Azarkhavarani et al (2019), and Horáčková et al (2018) could be due to the high temperature storage. As high cell metabolism and harmful biochemical reaction could occur in probiotics under high temperatures, it could subsequently lead to cell death…”
mentioning
confidence: 83%
“…Hence, the difference in probiotic's survivability under refrigerated storage could be due to the phytochemicals that are present in the fruits. Similarly, since the pH of the nondairy beverages in the Shehata et al (2019) study was not reported, the low viability of the encapsulated probiotic could be affected by the phytochemicals in fruit beverages.…”
Section: S Tor Ag E S Tab Ilit Y Of MI Croen C Apsul Ated Prob I Oti C S In Nondairy B E Ver Ag E Smentioning
confidence: 95%
See 1 more Smart Citation
“…However, this problem has been solved by incorporating natural extracts such as moringa and green tea into the microcapsules containing the microorganisms. This promotes viability upon addition to fruit juice (kiwi, prickly pear, and carrot) and to yogurt and increases the stability of the microcapsules and viability of microorganisms with the incorporation of oligofructose or other prebiotics, such as inulin and fructo-oligosaccharides [ 12 , 13 , 14 ]. In other studies, both fruit juice and probiotics are incorporated into the microcapsule, which gives it more stability and allows the development of functional powdered beverages [ 64 ].…”
Section: Microcapsules In Functional Foodsmentioning
confidence: 99%